Pyramid Pest-Control Community-Ecosystem-Management as an Effort to Prevent Leptospirosis - Sukendra, Dyah Mahendrasari; Indrawati, Fitri; Puspita Santik, Yunita Dyah; Isnaini, Dewi Nur; Pratiwi, Eka Dian; Abdillah, Azizah Nur; Ash Shiddieqy, Muhammad Hasbi (Jurnal Abdimas, 2023)
Klaten Regency has the highest cases in Central Java during the last 3 years. Leptospirosis IR has increased 3-fold compared to 2021. In 2022, there will be 80 cases with CFR of 7.5% IR of 6.27/100,000 population, this figure exceeds the national maximum target (≤3/100,000 population). Juwiring is one of the sub-districts with a rapid increase in leptospirosis cases. This study aims to determine differences in the level of knowledge of PKK mothers regarding leptospirosis and efforts to prevent the increase in leptospirosis cases in Bulurejo through Pyramid Pest-Control Community-Ecosystem-Management. The research was conducted in July – August 2023. This research used a pre-experimental approach with one group pretest – posttest design. The research sample consisted of PKK mothers in Bulurejo, Juwiring District, Klaten Regency. Data analysis was performed using Wilcoxon test. The results obtained are p-value 0.001 indicating there is a difference in increasing knowledge before and after being given counseling activities. Counseling activities can have a positive effect on increasing the knowledge of PKK mothers regarding leptospirosis prevention.